A construção de práticas de leitura a partir do material didático utilizado no sistema educacional socioeducativo feminino de Porto Velho - Santos, Geniele Brandão dos (2023)
This dissertation presents an analysis of the development of reading skills among adolescents in conflict with the law in compliance with provisional socio-educational measures and sentenced in the female context. The research had the general objective of analyzing the material teaching method used in an Inpatient Unit in the city of Porto Velho, unfolding specific objectives: initially, we investigated the teaching of speech genres in socio-educational educational system, dialoguing with the concepts of Kleiman (2002), which highlights the importance of social practice in the construction of linguistic knowledge; right away, we sought to understand how the educational axes of the National Common Curricular Base (BNCC) are integrated into the teaching of reading in Portuguese language classes for this group. At this point, studies by Bakhtin (2011) were taken as a reference, emphasizing the influence of the social context in the construction of meanings and discursive interaction, and by Fiorin (2006), with a view to deepening the understanding of the discursive and linguistic practices present in teaching reading. The study aims to adapt curricular guidelines to specific needs of adolescents, incorporating the ideas of Marcuschi (2010), which highlights the importance of inclusive education and consideration of diversities. Contributing with proposals for activities and approaches for developing reading skills, the research is based in the conclusions of the analysis of the teaching material, in line with the ideas of Elli Benincá (1994), which advocates action, reflection and pedagogical interventions as essential elements. Per Finally, we sought not only to understand the dynamics of teaching reading in this context challenging, but also improve pedagogical practices, promoting opportunities more inclusive and effective educational programs for the adolescents in question, aligning with the vision from different theorists who enrich and support this field of studies.